Environmental Pollution Factors in Household and Non-Communicable Diseases in Elderly - Tienthong, Thanate; Sripo, Narisara; Kaewboonchoo, Orawan (The Journal of Chulabhorn Royal Academy, 2022)
Environmental pollution factors in household are one of the factors that have empirical evidence showing their association as a risk factor for non-communicable diseases such as coronary heart disease, cancer, chronic respiratory disease, diabetes, and obesity. Currently, non-communicable diseases have a tendency to increase incidence and premature mortality in world population and Thailand. The content of this article is a review of the literature on residential household pollution and the incidence of chronic non-communicable diseases among the elderly. A review of literature found that household pollution is a risk factor for non-communicable diseases such as Particulate matter, Nitrogen dioxide, Volatile organic compounds (VCs), Polycyclic aromatic hydrocarbons, Radon, Pesticides, Carbon monoxide, Aerosols, Sulfur dioxide, Phthalates, and heavy metal. The pollution originates from human livelihood and inappropriate health behaviors such as smoking. The reduction of environmental factors may prevent the non-communicable diseases, increase quality of life and reduce the rate of morbidity and premature mortality in Thailand aging society.